Semiquantitative evaluation of ophthalmic collateral flow in carotid artery occlusion: ultrasonic doppler study. Issue 12 (December 1979) - Kaneda, H; Irino, T; Watanabe, M; Kadota, E; Taneda, M
Abstract : The reliability of quantitative evaluation by doppler ultrasound with regard to the ophthalmic collateral blood flow in patients with carotid artery occlusion was estimated. The ultrasonic doppler flow signals of the ophthalmic collateral flow of 54 carotid occlusions were classified into four types and three degrees–high, moderate, and low reversed flow patterns–and were compared with the angiographic findings of the collateral flow classified into three grades–good, poor, and none. With the exception of three cases, the ultrasonic doppler flow patterns of the collateral flow correlated well with the angiographic findings in 54 occluded carotid arteries.